COMMON ERRORS IN TRANSLATION OF LABORATORY EQUIPMENT MANUAL IN AN ESP CLASS - Juita, Erlinna (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2021)
Industrial revolution 4.0 provided greater opportunities for digital technologies. Therefore, English is essentially needed especially in health sciences since it serves as language of instruction in guidelines published by WHO, recent updates in research journals, and the like. Consequently, English had been a compulsory subject in institutions of higher learning. In medical laboratory technology, English is needed to be applicable in comprehension of laboratory equipment manuals. The purpose of this study was to analyze common errors in translation of laboratory equipment manuals in an ESP class. This was a descriptive quantitative study. Data were obtained from assessment of 34 translation works performed by students in an ESP class. This study used authentic materials. There were four common problems identified in this study, word-choice problems, grammatical problems, pragmatic problems, and cultural issue. Grammatical problems became the cases with highest occurrence ranging from 82.35 – 97.6% among the errors found in the translation performed by the students.